Arecoline, a main alkaloid in Areca catechu, induces biological changes in human papillomavirus 16-positive cervical cancer cells via upregulation of viral oncogenes and cellular transcriptional factors - Jureeporn Chuerduangphui; Chaleampol Loymunkong; Tipaya Ekalaksananan; Chamsai Pientong (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the effects of arecoline on HPV-positive cervical cells and unveil its underlying mechanism in cervical carcinogenesis. Methods: The cytotoxicity of arecoline was determined and the effect of subtoxic concentrations of arecoline on the expression of viral oncoproteins and transcriptional factors was examined in CaSki and SiHa cells. HPV16 promoter activity was evaluated in a plasmid containing HPV16 long control region (pGL3-HPV16LCR)-transfected cells. Cell proliferation, cell migration, and number of colonies were assessed by MTT, wound healing assay, and colonyforming assay, respectively. Results: Arecoline at 0.01 μg/mL significantly upregulated HPV16 E6 and E7 oncoproteins in both CaSki and SiHa cells. It also upregulated the expression level of c-Fos and c-Jun mRNAs, and c-Myc protein in CaSki and SiHa cells. In addition, arecoline at subtoxic concentrations (0.002 5 and 0.01 μg/mL) significantly induced HPV16 promoter activity in pGL3-16LCR-transfected cells. It also promoted SiHa and CaSki cell proliferation, migration, and colony formation. Conclusions: Arecoline at subtoxic concentrations promotes the proliferation, migration, and colony formation of CaSki and SiHa cells via upregulation of c-Fos, c-Jun, c-Myc, and HPV16 E6 and E7 expressions.